Effective Strategies to Prevent the Three Major Educational Sins: An Implementation Analysis in Elementary Schools - Akhmad Hanama; Dian Hidayati (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines the implementation of prevention programs for three major educational challenges in elementary schools through a literature review. Using Miles and Huberman's qualitative data analysis, the study follows four stages: data collection, data reduction, data display, and conclusion drawing. Findings suggest that prevention can be effectively achieved through targeted socialization, counseling programs, and character education. These initiatives aim to instill positive values and enhance student awareness, fostering an ethical and disciplined educational environment. The study highlights the importance of proactive measures and integrating prevention strategies into school programs to promote holistic student development